Workability and Strength Performance of Foamed Palm Oil Waste Concrete - Muhammad Hariz, Mohamed Idris; Khairunisa, Muthusamy; Rokaih, Othman; Nur Azzimah, Zamri; Muhammad Nazrin Akmal, Ahmad Zawawi; Nasly, Mohamed Ali (PIBEC 2016, 2016)
Palm oil industry is one of the most promising and rapidly growing industries Malaysia. However, lots of by-products are generated such as palm oil clinker (POC) and palm oil fuel ash (POFA) which end up being dumped and left untreated in dumping area which results in environmental pollution. With the increasing amount of palm oil wastes generated annually, incorporation of POC and POFA in concrete production can provide a good solution to overcome this problem. The currents research investigates the effect of palm oil fuel ash when added as partial cement replacement towards workability, density and strength performance of palm oil clinker foamed concrete. A total of six mixes were used in this experimental work. Palm oil clinker concrete produced using 100% ordinary Portland cement were considered as control specimen. The rest of the mixes contain POFA as partial cement replacement 10%, 20%, 30%, 40% and 50%. All specimens are produced in 100 x 100 mm cubes and is subjected to water curing before subjected to compressive test on 7 and 28 days. The finding shows that workability of concrete decreases when the amount of POFA added is increased. In terms of strength performance, foamed concrete containing 10% of POFA exhibit the highest compressive strength of all specimens.